Elaboração de planejamento estratégico participativo na gestão do serviço de enfermagem de um hospital privado de Caxias do Sul/RS - Bertuol, Isabel Cristina de Souza (Universidade do Vale do Rio dos Sinos, 2016)
This study is a qualitative approach - linked to the line of research Health Care Nursing of the postgraduate studies Program of Universidade do Vale do Rio dos Sinos - Professional Master's level in Nursing. Its objective is the development of a participatory strategic planning seeking to translate and align the strategy and the institutional vision to the Nursing Service for the qualification of the work units that make up the organizational structure of a Private Hospital in the city of Caxias do Sul – Rio Grande do Sul. The research covered the proposition to build a strategic planning for the nursing service with the participation of nurses who form the service. The stages of construction contemplated the definition of the mission, vision and values that guide the nursing practice; the survey and analysis of strengths, weaknesses, threats and opportunities that interfere in the nursing service; the construction of the strategic service map using the Balanced Scorecard; the business description of the care units and the construction of the action plan. Participated in the study nine nurses who make up the nursing service in assistential and administrative functions. The data collection was performed using the Joint Application Design methodology, which promotes group work involving professionals in the discussion of an issue producing synergistic solutions and a strong confidence in the successful implementation of the work. The construction of the plan took place through meetings that were recorded, transcribed and after subjected to content analysis proposed by Bardin (2011). It was developed, the collective construction of the strategic objectives defined in the strategic service map from the alignment with the corporate strategy and the analysis of strengths, weaknesses, opportunities and threats, defined from the analysis of internal and external scenarios. The business description was made based on the Falconi model (2004), of the adult inpatient units and pediatric, surgical block, obstetric center, emergency, adult, neonatal and pediatric intense care units and the diagnostic imaging sector. The action plan was developed from the defined strategic objectives and contemplated actions for the education and development of the people who make up the service, satisfaction and internal environment, innovation and updating, work processes and management. The work enabled the development and appreciation of the professional nurses in the structuring of the nursing service promoting greater organization, credibility and visibility to the nursing work.
Keywords: Enfermagem; Planejamento estratégico participativo; Serviço de enfermagem; Nursing; Participatory planning strategic; Service of Nursing; ACCNPQ::Ciências da Saúde::Enfermagem